Effect of levothyroxine replacement therapy in patients with subclinical hypothyroidism and chronic heart failure: A systematic review - Triggiani, Vincenzo; Cittadini, Antonio; Lisco, Giuseppe (Frontiers in Endocrinology, 2022)
Background Chronic heart failure (CHF) affects the health care system with high social and economic costs due to recurrent hospital admissions or frequent ambulatory reassessments. Subclinical hypothyroidism (SCH) is commonly observed in patients with CHF and negatively affects myocardial function and remodeling and, ultimately, increases the risk of hospitalizations and all-cause and cardiovascular (CV) mortality. The role of levothyroxine replacement on relevant CV outcomes in patients with SCH and CHF is unclear. Objective To assess the effect of levothyroxine (compared to placebo or no treatment) on the incidence of all-cause and CV mortality, major adverse CV events, and heart failure in patients with SCH and CHF. Methods PubMed/MEDLINE, Cochrane Library, and ClinicalTrial.gov were searched for randomized clinical trials, non-randomized observational, multicentric, and comparative studies. No language restrictions were included. After duplicate removal, articles were screened and extracted for the synthesis according to a hierarchical strategy that included title, abstract, and full-text appraisal. The risk of bias was assessed by RoB2 and ROBIN-I tools. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology was applied to rate the quality of evidence and grade the strength of recommendations. Results Two trials were included in the systematic review with considerable indirectness and inaccuracy that down-graded the level of evidence. Discussion No evidence supports the use of levothyroxine for treating SCH in CHF due to the lack of reliable and well-designed clinical trials. Conclusion CV outcome and dose-response trials are needed to understand better the role of levothyroxine replacement treatment for a safer prescription in this clinical setting.